The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/pce.12716
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopic composition of forest soil respiration in the decade following bark beetle and stem girdling disturbances in the Rocky Mountains

Abstract: Bark beetle outbreaks are widespread in western North American forests, reducing primary productivity and transpiration, leading to forest mortality across large areas and altering ecosystem carbon cycling. Here the carbon isotope composition (δ 13 C) of soil respiration (δ J ) was monitored in the decade after disturbance for forests affected naturally by mountain pine beetle infestation and artificially by stem girdling. The seasonal mean δ J changed along both chronosequences. We found (a) enrichment of δ J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
(231 reference statements)
2
8
0
Order By: Relevance
“…Our study suggests that the environmental factors limiting microbial function shift depending on whether fire or pathogeninduced mortality is the disturbance agent. Our results are consistent with studies limited to single disturbances [31,32,40,50,92,94]. Soil biogeochemical processes can be represented through a variety of modeling approaches including a simple bulk substrate, moisture and Q10 response [105], a more complex treatment of soil substrate suitability [62,106], or even trait-based approaches [107,108].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study suggests that the environmental factors limiting microbial function shift depending on whether fire or pathogeninduced mortality is the disturbance agent. Our results are consistent with studies limited to single disturbances [31,32,40,50,92,94]. Soil biogeochemical processes can be represented through a variety of modeling approaches including a simple bulk substrate, moisture and Q10 response [105], a more complex treatment of soil substrate suitability [62,106], or even trait-based approaches [107,108].…”
Section: Discussionsupporting
confidence: 78%
“…Both disturbances contribute enough variation to the environmental drivers of microbial function to reduce the importance of topography and its correlates as determinants of the rates of CO 2 efflux and potential enzyme activities (Table 1). While beetle mortality alone may be complicated by the timing of when that mortality occurred [31,93,94], the environmental correlates of microbial function after fire alone (pH and DOC/TDN) are not the same as the correlates after compounded beetles and fire disturbance (DOC/TDN). In our previous work [32] and this current study, we have found limited effects of beetle mortality on soil pH itself, though we find some evidence that beetle kill apparently buffers soil pH (Figures 2e and A3).…”
Section: Discussionmentioning
confidence: 99%
“…We did not collect location‐specific C a or δ a , and thus, we assumed that both values were homogenous across the study site. Previous studies have demonstrated that the variability of C a or δ a is negligible compared to the much larger variability of these quantities in the soil [ Riveros‐Iregui et al ., ; Bowling et al ., ; Mauer et al , ]. We then calculated the intercept of the regression ( δ R ) as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…This is largely ascribed to the rapid accumulation of tree biomass in the plantations (Chen et al 2017). Soil LOC includes low-molecular-weight compounds from plant rhizodeposition, C leachates and decomposition products from plant litter, and microbial biomass (Jones et al 2004, Maurer et al 2016, and thus, the highly active C pool can be closely related to both soil heterotrophic respiration and soil C sequestration (K€ ogel-Knabner 2002). One of the key obstacles is that the huge background pool of soil organic carbon (SOC) is likely to impede the ready detection of SOC changes.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose to explore SOC changes by monitoring the dynamics of soil labile organic carbon (LOC). Soil LOC includes low-molecular-weight compounds from plant rhizodeposition, C leachates and decomposition products from plant litter, and microbial biomass (Jones et al 2004, Maurer et al 2016, and thus, the highly active C pool can be closely related to both soil heterotrophic respiration and soil C sequestration (K€ ogel-Knabner 2002). As a result, changes in soil LOC concentration and/or turnover time may sensitively reflect changes in the C retention in soils (Cleveland et al 2007, Rousk et al 2016.…”
Section: Introductionmentioning
confidence: 99%